Development of a nutrition knowledge questionnaire for young endurance athletes and their coaches. (23rd October 2017) - Heikkilä, M.; Valve, R.; Lehtovirta, M.; Fogelholm, M.
Abstract : Both athletes and coaches should have adequate nutrition knowledge to understand the importance of diet on athletic performance, recovery, and health. Nutrition knowledge can be assessed reliably only by validated knowledge questionnaires. The aim of this study was to develop a reliable and valid questionnaire for assessing the nutrition knowledge of young endurance athletes and their coaches. The questionnaire was developed with an expert panel and pilot tested by athletes, coaches, and students. Content, face, and construct validities both as test‐retest reliability and internal consistency reliability were ensured when the current questionnaire was developed. Athletes (n = 16) and coaches (n = 13) pilot tested the 127‐item questionnaire. After item analysis and proposals from the expert panel, 41 items were removed. Internal consistency of the 86‐item questionnaire in the pilot study was 0.87, measured using Cronbach's α. Construct validity was evaluated by the difference in knowledge between nutrition (n = 20) and humanities students (n = 22). Nutrition students had significantly higher knowledge scores ( P < .001). Test‐retest reliability for all knowledge sections between those groups was 0.85 measured using Pearson's r . Final adjustments to the questionnaire were made on the grounds of feedback from the respondents and proposals from the experts (n = 6). These adjustments resulted in minor changes in the construct of the items, the layout of the questionnaire, and the removal of 7 items. The final questionnaire had 79 items. The questionnaire can be used to measure the overall nutrition knowledge of endurance athletes and their coaches and to find potential gaps in nutrition knowledge.